Pengalaman Guru dalam Mendesain Pembelajaran IPS Berbasis Kearifan Lokal di Sekolah Dasar - Treesly Y.N Adoe; Taty R. Koroh; Vera R Bulu; Markus Sampe (FKIP UNSULTRA, 2025)
This study aims to explore teachers’ experiences in designing Social Studies learning based on local wisdom in elementary schools. The study employed a qualitative approach with a phenomenological design to understand teachers’ subjective experiences in understanding, designing, and implementing Social Studies learning that integrates local sociocultural contexts. The participants consisted of elementary school teachers and a school principal who had experience implementing learning based on the local social and cultural environment. Data were collected through in-depth interviews, classroom observations, and documentation of teaching modules, learning materials, instructional media, and students’ assignments. Data were analyzed through data condensation, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings show that teachers understand local wisdom as a learning resource encompassing culture, history, social values, economic activities, community habits, and everyday social life. Teachers’ strategies included utilizing the surrounding environment, local stories, observation, discussion, and students’ personal experiences. However, implementation still faced several challenges, including limited references, teaching materials, time, facilities, and institutional support. Phenomenologically, teachers’ experiences indicate that local wisdom-based Social Studies learning is understood as a pedagogical adaptation process that connects the curriculum with students’ lived realities. This study emphasizes the importance of teacher creativity and school support in developing Social Studies learning that is contextual, meaningful, and rooted in the sociocultural life of the community.